2012
DOI: 10.3324/haematol.2012.068965
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the severity of hemolysis, clinical manifestations and risk of death in 415 patients with sickle cell anemia in the US and Europe

Abstract: 464haematologica | 2013; 98(3)The intensity of hemolytic anemia has been proposed as an independent risk factor for the development of certain clinical complications of sickle cell disease, such as pulmonary hypertension, hypoxemia and cutaneous leg ulceration. A composite variable derived from several individual markers of hemolysis could facilitate studies of the underlying mechanisms of hemolysis. In this study, we assessed the association of hemolysis with outcomes in sickle cell anemia. A hemolytic compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
175
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(197 citation statements)
references
References 50 publications
15
175
3
1
Order By: Relevance
“…The reasons for this lack of independent association are unknown, but Quinn et al observed that the level of anemia explained only 5% of the arterial oxygen desaturation variability in SS/Sb 0 thalassemia children, and suggested that anemia was not the main factor explaining the presence of hemoglobin oxygen desaturation at rest. 5 Nevertheless, further studies using primary markers of hemolysis, such as life span, 40 or the recent integrated hemolytic marker validated by Nouraie et al, 44 are needed to definitively exclude a role of anemia in resting hemoglobin oxygen desaturation in SS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this lack of independent association are unknown, but Quinn et al observed that the level of anemia explained only 5% of the arterial oxygen desaturation variability in SS/Sb 0 thalassemia children, and suggested that anemia was not the main factor explaining the presence of hemoglobin oxygen desaturation at rest. 5 Nevertheless, further studies using primary markers of hemolysis, such as life span, 40 or the recent integrated hemolytic marker validated by Nouraie et al, 44 are needed to definitively exclude a role of anemia in resting hemoglobin oxygen desaturation in SS patients.…”
Section: Discussionmentioning
confidence: 99%
“…64,65 However, mortality is still significant once patients reach adulthood. 61,66 SCD-associated morbidity and mortality in young adults is largely due to as yet unpreventable complications such as priapism, avascular necrosis, chronic pulmonary impairment, hypertension, stroke and recurrent venoocclusive crises. 58,[67][68][69][70] The only curative approach for SCD is HSCT.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…14 PAH is epidemiologically linked to a high baseline rate of intravascular hemolysis in SCD. 15 Preclinical and human vascular studies have confirmed that hemolytic anemia leads to vasculopathy through decreased NO bioavailability due to NO scavenging by cell-free plasma hemoglobin, increased arginase 1 levels in plasma, and increased xanthine oxidase-mediated superoxide production. [16][17][18] Similar to patients with SCD, sickle cell mice with high baseline hemolysis have diminished responses to NO and NO donors and develop PAH as they age.…”
Section: Introductionmentioning
confidence: 99%